Novel groups of Gammaproteobacteria catalyse sulfur oxidation and carbon fixation in a coastal, intertidal sediment - Lenk, Sabine; Arnds, Julia; Zerjatke, Katrice; Musat, Niculina; Amann, Rudolf; Mußmann, Marc (Environmental microbiology, 2011)
The oxidation of hydrogen sulfide is essential to sulfur cycling in marine habitats. However, the role of microbial sulfur oxidation in marine sediments and the microorganisms involved are largely unknown, except for the filamentous, mat-forming bacteria. In this study we explored the diversity, abundance and activity of sulfur-oxidizing prokaryotes (SOP) in sulfidic intertidal sediments using 16S rRNA and functional gene sequence analyses, fluorescence in situ hybridization (FISH) and microautoradiography. The 16S rRNA gene analysis revealed that distinct clades of uncultured Gammaproteobacteria are important SOP in the tidal sediments. This was supported by the dominance of gammaproteobacterial sequences in clone libraries of genes encoding the reverse dissimilatory sulfite reductase (rDSR) and the adenosine phosphosulfate reductase (APR). Numerous sequences of all three genes grouped with uncultured autotrophic SOP. Accordingly, Gammaproteobacteria accounted for 40-70% of all ¹⁴CO₂-incorporating cells in surface sediments as shown by microautoradiography. Furthermore, phylogenetic analysis of all three genes consistently suggested a discrete population of SOP that was most closely related to the sulfur-oxidizing endosymbionts of the tubeworm Oligobrachia spp. FISH showed that members of this population (WS-Gam209 group) were abundant, reaching up to 1.3 × 10⁸ cells ml⁻¹ (4.6% of all cells). Approximately 25% of this population incorporated CO₂, consistent with a chemolithoautotrophic metabolism most likely based on sulfur oxidation. Thus, we hypothesize that novel, gammaproteobacterial SOP attached to sediment particles may play a more important role for sulfide removal and primary production in marine sediments than previously assumed.